1998
DOI: 10.1152/ajprenal.1998.274.2.f395
|View full text |Cite
|
Sign up to set email alerts
|

Localization of cytochromeP-450 4A isoforms along the rat nephron

Abstract: The expression of P-450 4A isoforms responsible for the formation of 20-hydroxyeicosatetraenoic acid (20-HETE) was examined using the reverse transcription and polymerase chain reaction in various nephron segments and preglomerular arterioles microdissected from the kidneys of Sprague-Dawley rats. Expression of cytochrome P-450 4A1, 4A2, 4A3, and 4A8 mRNA could be detected in RNA extracted from the whole kidney. The expression of P-450 4A1, 4A3, and 4A8 mRNA was similar in the kidney of male and female rats, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
119
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(123 citation statements)
references
References 27 publications
4
119
0
Order By: Relevance
“…Interestingly, these two human P450s exhibited the same highly specific pattern of distribution within the nephron and were not expressed in cells comprising the glomeruli, loops of Henle, or collecting tubules. Thus, the proximal tubular pars convoluta and pars recta segments represents the principal site for 20-HETE formation in the human kidney, an observation similar to that made in experimental animals (18,19,26,29). This pattern of CYP4F2 and CYP4A11 distribution in human kidney has, in all likelihood, important implications with regard to effects of AA-derived eicosanoids on integrated renal function.…”
Section: -Hete Formation By Human Renal P450 Enzymessupporting
confidence: 68%
See 2 more Smart Citations
“…Interestingly, these two human P450s exhibited the same highly specific pattern of distribution within the nephron and were not expressed in cells comprising the glomeruli, loops of Henle, or collecting tubules. Thus, the proximal tubular pars convoluta and pars recta segments represents the principal site for 20-HETE formation in the human kidney, an observation similar to that made in experimental animals (18,19,26,29). This pattern of CYP4F2 and CYP4A11 distribution in human kidney has, in all likelihood, important implications with regard to effects of AA-derived eicosanoids on integrated renal function.…”
Section: -Hete Formation By Human Renal P450 Enzymessupporting
confidence: 68%
“…Furthermore, since the proximal tubule is where most electrolyte and water reabsorption occurs (1), the capacity of 20-HETE to potently inhibit Na ϩ /K ϩ -ATPase activity in this region of the nephron probably contributes to its known natriuretic and diuretic effects (4,62,74). In rats, CYP4A expression and 20-HETE formation have also been noted in renal microvessels (19,29,75), another proposed site where this eicosanoid influences vascular tone, autoregulation of renal blood flow, and/or tubuloglomerular feedback (9,10). However, the absence of CYP4 enzymes from the human renal vasculature suggests that synthesis of 20-HETE exclusively within the proximal tubules is sufficient for this compound to elicit its potent effects on kidney function.…”
Section: -Hete Formation By Human Renal P450 Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the isoforms catalyze the ω-and ω-1 hydroxylation of arachidonic acid to produce 20-HETE [2,5,[25][26][27]. Ito et al [28] used isoform specific primers to amplify 4A isoforms individually and found that the expression of CYP4A1 mRNA was very low but that CYP 4A2 and 4A3 mRNA are constitutively expressed throughout various nephron segments and the renal vessels in male SD rats. Schwartzman and his colleagues [2] also demonstrated, by Northern blot analysis, that CYP 4A2 and 4A3 mRNA are constitutively expressed in rat kidney, whereas the expression of 4A1 mRNA is nearly undetectable in the kidney of 3 to 7-wk-old male SD rats.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated the presence of neuronal nitric oxide synthase (nNOS) [30], cyclooxygenase-2 (COX-2) [31], and cytochrome P 450 [32] in macula densa and adjoining ascending loop of Henle cells. Nitric oxide (NO), and arachidonic acid metabolites have been shown to exert modulating roles on the TGF mechanism as shown in figure 1.…”
Section: Effects Of Angiotensin II On Juxtaglomerular Apparatusmentioning
confidence: 99%